Peak inspiratory pressure requirements in infants born weighing less than 750 g. - Foote, K D (1990)
The possibility that peak inspiratory pressure requirements or the arterial:alveolar oxygen ratio can predict the clinical outcome in infants weighing less than 750 g at birth was explored in a consecutive series. Nine of 10 infants (90%) with a peak inspiratory pressure requirement of more than 18 cm H2O at 48 hours or more than 16 cm H2O at 72 hours from age subsequently died later of respiratory causes (defined as death after 72 hours of pulmonary interstitial emphysema, bronchopulmonary dysplasia, or cor pulmonale). Twenty of 21 remaining infants (95%) survived until discharge. Using these data a 95th centile for peak inspiratory pressure requirement during the first 72 hours of life was constructed. The potential value of this centile in predicting later death of respiratory causes was examined in a separate series. Twelve of 15 infants (80%) whose peak inspiratory pressure requirements remained below the 95th centile, or were not ventilated (n = 6), survived. In contrast, 11 of 12 (92%) infants whose requirements crossed the 95th centile died later of respiratory causes. The infants who died had more radiological changes and higher mean arterial carbon dioxide pressure than survivors suggesting that the severity of the initial lung disease rather than the way that ventilation was managed determined prognosis. Peak inspiratory pressure requirement was more useful than arterial:alveolar oxygen ratio in clearly distinguishing between survivors and infants who died later of respiratory causes.